Public perception on face mask wearing during COVID-19 pandemic in Malaysia: a cross sectional study - Yusof, Muhammad Zubir; Fadzil, Nur Faza Zinnirah; Kamaruzi, Nik Nur Niska Azlin; Ayazi, Maya Syazana Syamimi (Public Library of Science (PLOS ONE), 2024)
Introduction Since the emergence of COVID-19, the Malaysian government has made wearing a face mask in public mandatory since August 1, 2020, as an effort by the government to control the transmission of COVID-19. However, Malaysians’ willingness to wear face masks in public is unknown. Objective Thus, this study aimed to evaluate their perception of face mask wearing during COVID-19 and its contributing factors. Methodology A total of 1024 respondents, aged ≥ 18 years, participated in this online cross-sectional survey from October 2021 to December 2021. The Face Mask Perception Scale (FMPS) was used to measure their perceptions. Results Most of the respondents perceived wearing a face mask as uncomfortable. Our findings also revealed statistically significant differences and a small effect (f2 = 0.04) in which respondents who were concerned about being infected by the virus perceived face mask wearing appearance positively (B = - 0.09 units of log-transformed, 95% CI = - 0.15, - 0.04), whereas married respondents perceived it negatively (B = 0.07 units of log-transformed, 95% CI = 0.03, 0.09). There were no statistically significant differences in other domains of FMPS. Conclusion In conclusion, discomfort was a major complaint. Marital status and fear of COVID-19 infection affected their perceptions. The public health implications of these findings highlight the importance of addressing discomfort and societal perceptions, particularly those influenced by factors such as marital status and COVID-19 experience, to promote widespread acceptance and consistent usage of face masks, which is crucial in mitigating the spread of COVID-19.